Fundacje, media, etyka. Ciąg dalszy rozważań - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2008)
The object of my last year’s presentation were communication (ethical, integration, political) threats posed by a foundation seen as an extension to a company in its traditional sense. I came to the conclusion that an automatic transfer of social trust capital to the parent company (in certain, specified by me, contexts) causes the foundation to betray its mission. It is the company that becomes the main beneficiary of mutual aid activities. This year, the paper addresses the following three issues. Firstly, I intend to show the symbolic pressure exerted on both consumers and producers, which is made possible by the ‘labeling’ of products of ‘socially sensitive’ companies. There would be no point questioning the fact of shaping social attitudes if it weren’t for an ambiguous position of the co-ordinator of the enterprise, who becomes vested with the rights of a certification authority. Another question under consideration is the transformation of a foundation into a quasi-company. A third-sector organization adds business activity to the goals specified in its by-laws. It results in taking on highly-skilled professionals who have nothing to do with charitable activity of a third sector organization. Finally, there is a danger of a foundation’s approximation to a second-sector organization. A foundation may be financed by a public administration body. This may lead to the division of the final product of a foundation between the beneficiaries and the body which sponsors its operation using a ‘lump sum’ payment. Whichever the problem, the key aspect seems societal control over mutual aid activities. Its lack results in an abuse of power and the diminished trust of the manipulated society in effective cooperation.